(untitled) (Brazilian Journal of Radiation Sciences, 2021)
High-resolution diffractometer is one of the first instruments of the set of 15 priority neutron scattering instruments to be installed at the Brazilian Multipurpose Reactor (RMB). A basic project of this instrument consists of the existence of three guides through which neutrons pass from source to sample to guarantee maximum neutron flux at the sample position. In this study, we investigate guide geometry performance considering fixed diffractometer geometry and spatial arrangement. Comparisons between different guide shapes and supermirrors are performed using software based on the Monte Carlo method, McStas. Our conclusion shows that a better solution is splitting the initial flux into two different guides to obtain the maximum flux at the sample position.